Body shots : early cinema's incarnations - Auerbach, Jonathan, 1954- (University of California Press, 2007)
Argues that it was the human form in motion that most profoundly shaped early cinema. Situating his discussion in a political and historical context, the author begins his analysis with films that reveal striking anxieties and preoccupations about persons on public display. It also considers twentieth-century American incarnation of cinema itself.